Avaliação qualitativa da sustentabilidade na produção do Bioetanol: um caso comparativo entre a casca do coco e o bagaço da cana-de-açúcar - Melo, Larissa Pedrosa de (2021)
Brazil is a major global producer of biofuels, especially bioethanol. Its conventional production takes place through sugarcane, however, bioethanol produced from sugarcane bagasse is beginning to gain space in the Brazilian energy matrix, pointing to a growing trend. Furthermore, the country is a major agricultural producer, with the generation of lignocellulosic residues resulting from this production being abundant, such as coconut husk, whose generation exceeds 1.6 million tons per year. This dissertation aimed to carry out an assessment of sustainability comparing two production routes for second-generation bioethanol, one from sugarcane bagasse and the other from coconut husk. Initially, an exploratory and descriptive research was carried out, through which a survey was carried out regarding the production routes involving the two biomasses in question and the available sustainability assessment methodologies, identifying their respective indicators. Subsequently, through the analysis of the literature review, the two routes to be evaluated and the sustainability assessment methodology used were selected. Then, the definition of sustainability indicators that are related to the present study was made for their application on the selected routes. The productive route selected, from sugarcane bagasse, derives from the Iogen technology and is used at Raízen's Costa Pinto Plant, which produces the biofuel at a commercial level; for the coconut husk, a route developed on a bench scale was selected, which employs physical pre-treatment and chemical pre-treatment with NaOH, with subsequent enzymatic hydrolysis and fermentation. To assess the sustainability of these routes, the GBEP methodology was selected, which provides a qualitative treatment of data, from which 9 indicators were chosen. The results obtained from the analysis of the indicators indicated that although the route that uses sugarcane bagasse was identified as the largest recruiter of labor, the route that uses coconut husk showed greater social sustainability, for which was concluded to have better remuneration and a lower occurrence of occupational injuries, illnesses and deaths. With regard to environmental sustainability, with lower incidence of GHG emissions and less water extraction, the route via bagasse was superior to the coconut husk route. Regarding the economic pillar, with greater productivity, in addition to greater net income from production, despite higher energy expenditure, production via bagasse also revealed greater sustainability. The comparative analysis produced by data processing identified that the route via sugarcane bagasse is the most sustainable for the production of second-generation bioethanol.